Il ruolo del Design per la valorizzazione dei Musei d’Impresa nell’era digitale - Francesca Morelli (ZoneModa Journal, 2025)
In line with the latest trends, the museum system is increasingly integrating digital tools to enhance the visitor experience, making it more engaging, immersive, and interactive. The implementation of these digital solutions not only revitalizes the museum and sustains public interest, but also opens new perspectives for the future of museum experiences, making cultural heritage accessible to an increasingly broad and diverse audience. Focusing on the Corporate Fashion Museum, which embodies the environments of ‘heritage brands,’ this contribution seeks to identify the digital solutions, identities, and experiential strategies employed by enterprise museums to highlight their unique characteristics, values, and histories. Through an examination of current trends and an analysis of state-of-the-art case studies, this research underscores the significance of applied digital technologies, visual communication, display techniques, and exhibition approaches in creating a dynamic and engaging museum experience through the principles of design.